The Nature of Swedish-Russian Capital Flows - Torbjörn Becker (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2016)
This paper provides a detailed investigation of the investment flows between Russia and Sweden in the last decade and a half. The bilateral data consists of both aggregate macro data and company level greenfield and M&A FDI. The relatively large flows from Sweden to Russia and insignificant flows in the other direction support the hypotheses that investments tend to go from higher income countries to lower income countries and from smaller markets to larger. Investment flows have grown in line with trade, consistent with the idea that international investments and exports often are compliments rather than substitutes. The investments from Sweden to Russia also show that FDI has been a more stable source of foreign funding than portfolio flows as has been argued both in the theoretical and empirical literature; Whereas portfolio flows have declined significantly since the global crisis in 2008, the stock of FDI has continued to increase. The paper also argues that it is hard to predict aggregate bilateral flows with great precision, in particular for such a large economy as the Russian, and empirical models tend to generate expected flows from Sweden to Russia that are larger than the ones observed. In terms of reasons for FDI between the two countries, horizontal FDI seem to dominate by a wide margin. However, there are a few examples of vertical FDI in resource intensive sectors in Russia, and limited amounts of complex FDI in Sweden by Russian companies. In the challenging environment Russia is currently facing due to low international oil prices and sanctions it will be hard to attract new FDI. Although it may be tempting to use short-term tax exemptions or barriers to trade to induce FDI, sustainable long-run policies should focus on fundamental reforms of the institutions that reduce corruption, contribute to the rule of law and limit excess bureaucratic burdens. This will not only make Russia attractive to foreign investors but also encourage domestic innovators and entrepreneurs to help modernize and diversify the economy.
Keywords: F21; F23; F41; 330; FDI; Capital flows; Gravity model; Sweden; Russia